Sunday

February 1, 2015

February 1, 2015

Posted by **John** on Sunday, March 10, 2013 at 4:57pm.

- Calculus -
**Count Iblis**, Sunday, March 10, 2013 at 6:55pmHint:

For x > 0, you have

(sqrt(x) + 1)^3 - (sqrt(x) - 1)^3 =

6 x + 2

**Answer this Question**

**Related Questions**

Simple Calculus - Evaluate \displaystyle \lim_{x \to 0} \frac{\sqrt{2}x}{\sqrt{2...

Calculus - Evaluate the indefinite integral: 8x-x^2. I got this but I the ...

Math - Solve the puzzle =RIGHT(LEFT($B$2,84),1) =RIGHT(LEFT($B$2,17),1) =RIGHT(...

Calculus - Please look at my work below: Solve the initial-value problem. y'' + ...

Algebra - b=2, c+ sqrt of 13. Trying to find the length of the 3rd side. It is a...

Math Help please!! - Could someone show me how to solve these problems step by ...

Algebra - Solve for s: h=(square root of 3)times s/2 and solve for h V= (pi)r ...

math calculus please help! - l = lim as x approaches 0 of x/(the square root of...

Calculus - "Leave the answer as a definite integral, but indicate how it could ...

Math/Calculus - Solve the initial-value problem. Am I using the wrong value for ...